Gut microbiota changes in postmenopausal women with low bone density linked to serum amino acid metabolism - Becerra-Cervera, Adriana; Jiménez-Ortega, Rogelio F.; Aparicio-Bautista, Diana I.; Palacios-González, Berenice; Vela-Amieva, Marcela; Ibarra-González, Isabel; Canizales-Quinteros, Samuel; Salmerón, Jorge; Rivera-Paredez, Berenice; Velázquez-Cruz, Rafael (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe gut microbiota (GM) has been linked to changes in bone mineral density (BMD), potentially contributing to the development of osteopenia or osteoporosis. Although the relationship between specific bacterial taxa and bone remodeling has been documented in various populations, data on the Mexican population remain limited. This study aimed to analyze the changes in the taxonomic composition of GM associated with low BMD (osteopenia/osteoporosis) and explore potential mechanisms influencing bone metabolism in Mexican postmenopausal women.MethodsBMD was measured by dual-energy X-ray absorptiometry. GM composition was analyzed through 16S rRNA amplicon sequencing in Mexican postmenopausal women. Metabolic functions were predicted using PICRUSt2 based on KEGG pathways at hierarchy level 3. Serum amino acid (AA) concentrations were measured in a sub-sample using tandem mass spectrometry.ResultsOur findings indicated that beta diversity significantly differed among BMD groups (p<0.05). Women with low BMD showed higher relative abundances of Bacteroides, Parabacteroides, Barnesiella, Odoribacter, Sutterella, Butyricimonas, Coprobacter, Angelakisiella, and Oscillibacter. Functional prediction revealed differences in alanine, valine, leucine, and methionine-related metabolic pathways. These findings were supported by lower serum concentrations of valine, leucine, and methionine in the low BMD group compared to the normal BMD group (p<0.05).ConclusionThis study provides evidence of the relationship between GM composition and AA concentrations with changes in BMD. These findings highlight promising areas for the development of potential therapeutic interventions